MULTICULTURAL AND PEACE-THEMED TRADE BOOKS AS IMPETUS FOR INTERCULTURAL LEARNING: A NARRATIVE EXPLORATION INTO STUDENTS’ LIVED EXPERIENCES - Ida Musirini; Sary Silvhiany; Rita Inderawati (University of Kuningan, 2025)
In an increasingly interconnected world, fostering an understanding of multiculturalism and peace education is essential for shaping socially responsible individuals. Schools play a crucial role in equipping students with knowledge and values needed to appreciate diversity and promote harmonious coexistence. This study investigates the perspectives of secondary school students on multiculturalism and peace education through the lens of trade books, aiming to understand their grasp of multicultural concepts and how they perceive diversity's contribution to peace. Employing a qualitative narrative inquiry approach, this research engages eight-grade students from a public school in Sekayu, South Sumatra, purposefully selected for their diverse urban backgrounds to discuss issues of peace and diversity introduced in their English through the selection of trade books on these topics. Using semi-structured interviews, participants were encouraged to share personal narratives that manifested their complex understanding of multiculturalism. The findings reveal a multifaceted perspective: while students acknowledge diversity as a strength that fosters cooperation and mutual support, they are also attuned to the potential conflicts that diversity can incite. This duality encapsulates the critical roles of literature in cultivating social cohesion and understanding among students. Moreover, the research emphasized the necessity for supportive education practices that assist students in navigating and embracing cultural differences effectively. Ultimately, the study highlights the imperative for educational settings to facilitate constructive dialogues that enhance students' ability to thrive in a diverse society.